Facile green synthesis, optical and photocatalytic properties of zinc oxide nanosheets via microwave assisted hydrothermal technique - Al-Hazmi, Faten; Aal, Nadia Abdel; Al-Ghamdi, Ahmed A.; Alnowaiser, F.; Gafer, Zarah H.; Al-Sehemi, Abdullah G.; Yakuphanoğlu, Fahrettin (Springer, 2013)
Novel hexagonal two dimensional ZnO nanosheets were successfully and economically synthesized using zinc acetate and urea based on a facile microwave hydrothermal method. The structure, morphology and size of the ZnO nanosheets were investigated by X-ray diffraction (X-ray), field emission scanning electron microscopy (FESEM), energy dispersive analysis of x-ray (EDS), transmission electron microscopy (TEM), selected area electron diffraction (SAED) and Fourier transform infrared spectroscopy (FTIR). X-ray analysis showed that the obtained ZnO nanosheets are crystalline corresponding to the pure ZnO phase with an average particle size of 12 nm. Optical properties of ZnO nanosheets were investigated by UV-Vis absorption and photoluminescence (PL) techniques. The band gap energy of ZnO nanosheets was found to be 3.29 eV. The photoluminescence (PL) measurement shows a strong UV emission, blue emission and blue-green emission bands. ZnO nano sheets possess a higher photocatalytic activity leading to the degradation of methylene blue (MB). The ZnO nanosheets are expected to have new opportunities in vast research areas and for application in catalysts and optoelectronic devices.
Keywords: ZnO nanosheets; Microwave hydrothermal process; Microstructure; Optical and photo catalytic properties